Posible cambio climático debido a la explotación de agua subterránea en el Valle de Ojos Negros, Baja California - V. Miguel Ponce; O. Rafael García Cueto; Sezar Ercan (Investigaciones Geográficas, 2001)
A detailed annual analysis of the records of climatological variables for the Ojos Negros Valley, B. C, revealed a negative tendency for temperature, and positive tendency for precipitation, along the study period (1949-1993). The increasing groundwater extraction for agricultural use produces a change in the balance energy and a decrease in albedo. From these data, B is inferred that a change in evapotranspiration and a humidification of the local climate occur, hence affecting the analyzed climatological variables, A similar, although more moderate trend, was observed in two climatological stations located nearby which were used as control.